Skrivning som produktion og reproduktion: En empirisk undersøgelse af, hvorfor nogle gymnasielever er bedre til skriftlig dansk end andre - Trolle, Christine; Pors, Anna (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2019)
At the most simple level, Pierre Bourdieu’s notion of ’cultural capital’ pertains to knowledge of the dominant conceptual and normative codes inscribed in a culture. This article investigates how pupils’ differences in cultural capital are reproduced in their written assignments in Danish in upper secondary school, and how their teachers contribute to this reproduction in their evaluations. The investigation is organised into three parts: A first quantitative analysis based on a survey which investigates the correlation between the pupils’ levels of cultural capital and their grades in written assignments in Danish, a second qualitative analysis which examines how cultural capital is evident in three assignments and finally a quantitative analysis which categorizes the teachers’ evaluations into four categories to reveal if the teachers discriminate between pupils with low and high levels of cultural capital. In the first quantitative analysis, we find a strong and positive correlation between the pupils’ levels of cultural capital and their grades in written assignments in Danish. The quantitative analysis also suggests that the transition of cultural capital from parents to children, especially in the form of the parents’ communication with their children, has an effect on the children’s grades in written assignments in Danish. In the second qualitative analysis we find that the pupils’ cultural capital is evident in the way the pupils develop information in their assignments, and how they create continuity at the most general level. The results indicate that the pupils with high cultural capital are quicker to develop new information and create continuity. And finally, the last analysis indicates that the teachers contribute to the reproduction of cultural capital by giving an unequal amount and a different quality of feedback to the pupils with low and high cultural capital. This mostly benefits the pupils with a high level of cultural capital.